Relationship between Monocarboxylate Transporter 4 (MCT-4) Expression and Breast Cancer Clinicopathology and Subtype in Sanglah General Hospital, Denpasar, Indonesia - Gede Andry Nicolas Andry Nicolas; I Wayan Sudarsa; Putu Anda Tusta Adiputra; Desak Made Wihandani; I Gede Putu Supadmanaba (DiscoverSys Inc., 2022)
Background: Breast cancer is the second leading cause of death in women in developing countries. The activity of Warburg and Reverse-Warburg effects on breast cancer is reflected by the expression patterns of two molecules, namely caveolin-1 and Monocarboxylate Transporter-4 (MCT-4). MCT-4 is a transmembrane transport protein that transports lactate from the cytoplasm to the intercellular fluid.Method: This is a cross-sectional analytical study to determine the relationship between MCT-4 expression and breast cancer clinicopathology and subtypes. The study was conducted between April and May of 2020 with 62 breast cancer patients as samples in Sanglah General Hospital, Denpasar. Analysis was done with SPSS 25.Results: A logistic regression analysis was performed to analyze the relationship between the dependent variable (MCT-4) and the covariates (stage, grade, and subtype). Of the three variables significantly associated with MCT-4 expression, only clinical-stage and subtype (luminal and non-luminal) remained independently associated with MCT-4 expression. Analysis on the clinical stage and subtype variables showed an adjusted OR of 4.727 (p = 0.047; 95% CI: 1.109 - 21.922) and 17.850 (p = 0.009; 95% CI: 2.069 - 154.003) , respectively. This suggests that MCT-4 has a significant association with subtype and clinical-stage, increasing the risk of cancer stage progression and developing a more malignant (non-luminal) subtype.Conclusion: High MCT-4 expression was significantly associated with malignant subtypes, high histological-grade cancer and advanced breast cancer.